1978
DOI: 10.1042/bj1760899
|View full text |Cite
|
Sign up to set email alerts
|

Calcium ions and the regulation of NAD+-linked isocitrate dehydrogenase from the mitochondria of rat heart and other tissues

Abstract: The effects of Ca2+ on the activity of isocitrate dehydrogenase (NAD+) in extracts of rat heart mitochondria were explored in the presence of MgCl2 by using EGTA buffers. In the absence of ADP, Ca2+ (about 30 micrometer) resulted in a slight increase in apparent Km for threo-Ds-isocitrate; in the presence of ADP, Ca2+ (about 25 micrometer) greatly lowered the apparent Km for threo-Ds-isocitrate from 227 micrometer to 53 micrometer without changing the maximum velocity. At 100 micrometer-threo-Ds-isocitrate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
206
3
3

Year Published

1980
1980
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(227 citation statements)
references
References 29 publications
15
206
3
3
Order By: Relevance
“…The classical respiratory controlhypothesis of Chance and Williams [37] implies that the rate of respiration is regulated by the availability of ADP to the F 1 /F 0 -ATPase. This is based on the observation that when adding ADP to a suspension of isolated mitochondria, O 2 consumption increases ("state 3 respiration"), and when ADP and/or P i in the assay are consumed, the rate of respiration decreases again ("state 4 respiration" [53,54,56,57,127,128] (Fig. 3A and B), it was proposed that Ca 2+ rather than ADP may regulate respiration in vivo [106].…”
Section: Energy Supply and Demand Matchingmentioning
confidence: 99%
See 2 more Smart Citations
“…The classical respiratory controlhypothesis of Chance and Williams [37] implies that the rate of respiration is regulated by the availability of ADP to the F 1 /F 0 -ATPase. This is based on the observation that when adding ADP to a suspension of isolated mitochondria, O 2 consumption increases ("state 3 respiration"), and when ADP and/or P i in the assay are consumed, the rate of respiration decreases again ("state 4 respiration" [53,54,56,57,127,128] (Fig. 3A and B), it was proposed that Ca 2+ rather than ADP may regulate respiration in vivo [106].…”
Section: Energy Supply and Demand Matchingmentioning
confidence: 99%
“…This was associated with reduced pyruvate dehydrogenase (PDH) activity, whose K m for Ca 2+ activation is in the range of ∼650 nM to 1 µM ( Fig. 3B; [54,56,57,59,127,128]). Thus, both the reduced amplitude of cytosolic Ca 2+ transients [59] and elevated [Na + ] i [117] may hamper Ca 2+ -activation of TCA cycle enzymes in heart failure.…”
Section: Pathophysiological Aspects Defects In Ec Coupling In Chronicmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted that PDH and OGDH are inhibited by their end-products, acetylCoA and succinylCoA, respectively [26,27]. For further details see [9,[11][12][13]16,19,20, 3. remonstration of the ~a*~-sensitivity of the dehydrogenases when located within intact uncoupled mitochondria…”
Section: Elsevierfnorth-holland Biomedical Pressmentioning
confidence: 99%
“…They are pyruvate dehydrogenase (PDH), phosphate phosphatase [l] (whose activation increases amounts of active PDH (PDH. )), NAD+-isocitrate dehydrogenase [2] and oxoglutarate dehydrogenase (OGDH) [3]. Studies on rat heart [4-61, skeletal muscle [7,8] and adipose tissue [9] and pig lymphocytes [lo] have demonstrated that these enzymes can be activated within mitochondria (incubated with physiological concentrations of Mg2+ and Na+) by increases in extramitochondrial [Ca"] within the expected physiological range [l 11.…”
Section: Introductionmentioning
confidence: 99%